Disparities in Suicide and Mental Health among Student Athletes of Ethnic and Racial Minorities compared to their White Non-Latinx Counterparts - Elizabeth Russo Miss (Undergraduate Research Journal for the Human Sciences, 2024)
The present paper reviews literature examining trends among suicide, suicidal ideation, and mental illness rates in ethnic and racial marginalized communities’ student-athletes. While the rates of suicide amongst student athlete populations are lower than rates of suicide seen in the general student populations, there remains a discrepancy amongst rates of suicide in student athletes with those identifying with racial and ethnic minority backgrounds endorsing higher rates of suicidal ideation. Data from the existing literature consisted of White, Black, Hispanic/Latinx, Asian/ Pacific Islander, Multiracial, and Native American student-athletes. Studies suggest that ethnic and racially marginalized students are more susceptible to suicide, depression, and other mental health concerns compared to their white counterparts. Across the literature, White student athletes appeared to have more social and academic support from fellow classmates, university administration and professors, and staff within their athletic departments. Student athletes who did not identify as White endorsed higher rates of loneliness, felt ethnically and racially underrepresented within their athletic department, and endorsed lack of appropriate medical treatment for injuries by athletic department medical staff. Additionally, non-White student athletes receive less peer support and must balance additional stressors such as discrimination in contrast to their White/non-Latinx peers. Recommendations for athletic departments and mental health providers supporting student athletes who identify as racial and ethnic minorities are discussed.
Keywords: Suicide; Suicidal Ideation; Race; Ethnicity; Mental Health